Description of a new species of the genus Nomisia Dalmas, 1921 (Araneae: Gnaphosidae) from Turkey with some faunistical remarks - Seyyar, Osman; Ayyildiz, Nusret; Topçu, Aydin (Zootaxa, 2009)
Nomisia anatolica sp. n. is described and illustrated from Turkey. Morphological features and detailed description based on collected material of Nomisia orientalis Dalmas, 1921 are presented. Nomisia negebensis Levy, 1995 is recorded for the first time from Turkey.